2009
DOI: 10.1186/1743-422x-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic studies reveal existence of multiple lineages of a single genotype of DENV-1 (genotype III) in India during 1956–2007

Abstract: Background: Dengue virus type 1 (DENV-1) have been mostly circulating silently with dominant serotypes DENV-2 and DENV-3 in India. However recent times have marked an increase in DENV-1 circulation in yearly outbreaks. Many studies have not been carried out on this virus type, leaving a lacunae pertaining to the circulating genotypes, since its earliest report in India. In the present study, we sequenced CprM gene junction of 13 DENV-1 isolated from Delhi and Gwalior (North India) between 2001-2007 and one 195… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
97
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 21 publications
6
97
0
Order By: Relevance
“…Similar findings were reported on the basis of shorter sequences in the Core-prM region (Dash et al, 2004 andKukreti et al, 2009). Emergence of DENV-3 (GIII) was reported in the 2005 outbreak in Northern India (Dash et al, 2006;Gupta et al, 2006).…”
Section: Introductionsupporting
confidence: 75%
“…Similar findings were reported on the basis of shorter sequences in the Core-prM region (Dash et al, 2004 andKukreti et al, 2009). Emergence of DENV-3 (GIII) was reported in the 2005 outbreak in Northern India (Dash et al, 2006;Gupta et al, 2006).…”
Section: Introductionsupporting
confidence: 75%
“…18 Study in India in 2006 concludes that reappearance of DENV-3 replaces the DENV-2 circulating a sign of outbreak. 19 This is reinforced from study by Prasetyowati and Astuti, 20 that the predominant serotype of dengue virus found in highly endemic areas are DEN 3 then followed DEN 2. Other data from various studies in several countries describe a unique, in which each serotype of dengue virus will trigger an outbreak based on geographical conditions and different time periods, for example serotype circulating in Bangkok is always different in each period.…”
Section: Discussionmentioning
confidence: 88%
“…2), closely related to the Delhi strains reported in 2006 (Kukreti et al, 2009). This serotype has been reported to be circulating in different regions of the country to a lesser extent since its first report from Vellore in south India in 1956.…”
Section: Discussionmentioning
confidence: 95%